THE RELATIONSHIP BETWEEN BODY MASS INDEX (BMI) AND HYPERTENSION ON ELDERLY IN MUHAMMADIYAH REGIONAL LEADERS OFFICE (PDM) OF SLEMAN - Ega Via Ambarwati; Indriani; Agus Riyanto (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2023)
Abstract Background: Hypertension is a non-communicable disease (NCD) which is the main cause of death globally. The prevalence of hypertension continues to increase and is often known as